The millipede genus Epanerchodus Attems, 1901 in continental China, with descriptions of seven new cavernicolous species (Diplopoda, Polydesmida, Polydesmidae) - Liu, Weixin; Golovatch, Sergei (Zootaxa, 2018)
Seven new species of Epanerchodus Attems, 1901 are described from caves in southern China: Epanerchodus latus n. sp., Epanerchodus tujiaphilus n. sp., Epanerchodus jiangxiensis n. sp., Epanerchodus coniger n. sp., Epanerchodus parvus n. sp., Epanerchodus gladiatus n. sp. and Epanerchodus chutou n. sp. The first three species are from Chongqing, Hunan and Jiangxi, respectively; the last four are from Guizhou. Additional records, illustrations and descriptive notes are given for the following troglobitic species: Epanerchodus lipsae Golovatch & Geoffroy, 2014, from Sichuan; Epanerchodus soror Geoffroy & Golovatch, 2004, from Yunnan; Epanerchodus stylotarseus Chen & Zhang, 1990, from Guizhou; Epanerchodus varius Geoffroy & Golovatch, 2004, from Hubei, Sichuan and Chongqing; and Epanerchodus draco Geoffroy & Golovatch, 2004, from Yunnan and Guizhou. New records of E. varius from Chongqing and E. draco from Guizhou are documented. A key and distribution maps are provided to all 25 species of Epanerchodus currently known to occur in mainland China.